Study on Identification of Rats and the Existence of Leptospira Bacteria. sp in the Flood Area of Puskesmas Tempe, Wajo District - Dr. Syamsuar; Dr. Hasnawati Amqam; Dr. Anwar Daud; Dr. Ida Leida Maria; Dr. Muh. Hatta; Dr. La Ode Muhammad Mursyafah (Asian Journal of Medical Research, 2018)
Background: Leptospirosis is one of the emerging infectious diseases caused by pathogenic bacteria called Leptospira and is transmitted from animals to humans (zoonosis). Mice as one of the reservoirs of leptospira bacteria found in urine and kidney. The aim of the study was to determining the presence of leptospira bacteria in rats in the flood prone area surrounding Community Health Center (Puskesmas) of Tempe, Wajo Regency. Subjects and Methods: The type of research used is descriptive research with observational approach. The samples in the study were rats caught with life trap in flood prone areas of Puskesmas Tempe area. Sampling is done by accidental sampling technique. Processing and data analysis is done by descriptive method and the kidney sample of the rattus was determined by PCR in the laboratory. Results: This study indicates that from the seven trapped rats, the types of rats in flood prone in Puskesmas Tempe area, Laelo and Salomenraleng villages, were Rattus tanezumi, Rattus norvegicus, Rattus Tiomanicus, which is none of them infected by Leptospira sp. Conclusion: In conclusion, the types of rats in flood-prone areas in the Tempe Community Health Center working area are Rattus tanezumi, Rattus norvegicus, Rattus Tiomanicus negatively contains leptopspira bacteria.  Further research is needed with more samples, not only in the parameter areas but also in buffers with more sensitive methods.